2020
DOI: 10.1186/s12903-020-01121-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of LTF, ENAM, and AMELX polymorphisms with dental caries susceptibility: a meta-analysis

Abstract: Background: This meta-analysis evaluated the association of LTF, ENAM, and AMELX polymorphisms with dental caries susceptibility. Methods: We searched the Scopus, PubMed/Medline, Web of Science, and Cochrane Library databases to retrieve articles published by October 2019. Review Manager 5.3 software was used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs). The results of publication bias tests were retrieved by Comprehensive Meta-Analysis 2.0 software. Results: A total of 150 relevant rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In a meta-analysis that included 4 studies [38,[48][49][50], Sharifi et al [51] did not prove any significant association between the SNPs in AMELX (rs946252 or rs17878486) and dental caries. Sensitivity analysis, however, indicated that AMELX (rs17878486) could be a risk factor for dental caries, which might have been hidden by other effective factors, namely, the ethnicity and type of selected controls.…”
Section: Discussionmentioning
confidence: 96%
“…In a meta-analysis that included 4 studies [38,[48][49][50], Sharifi et al [51] did not prove any significant association between the SNPs in AMELX (rs946252 or rs17878486) and dental caries. Sensitivity analysis, however, indicated that AMELX (rs17878486) could be a risk factor for dental caries, which might have been hidden by other effective factors, namely, the ethnicity and type of selected controls.…”
Section: Discussionmentioning
confidence: 96%
“…Sharifi et al [ 13 ] in a meta-analysis study found that ENAM rs3796704 polymorphism, especially in the Caucasus ethnic group and in studies with caries-free individuals as a control group, had a higher risk of caries, but they found no association between polymorphisms LTF rs1126478, ENAM (rs1264848 and rs3796703), and AMELX (rs946252, rs17878486, and rs2106416) and susceptibility to dental caries. However, sensitivity analysis showed that AMELX rs17878486 polymorphism can be a risk factor for dental caries, but race and type of the control group are the factors influencing the relationship between AMELX rs17878486 polymorphism and the risk of dental caries.…”
Section: Discussionmentioning
confidence: 99%